A kitchen in Italy : a year of family meals and celebrations from our home - Thorisson, Mimi (Clarkson Potter/Publishers, 2025)
"Discover the rich culinary treasures of Italian cuisine in this personal, transportive collection of 100 simple yet elegant recipes from the award-winning author of Old World Italian. Mimi Thorisson first captivated readers with A Kitchen in France, which displayed her family's idyllic lifestyle in the French countryside and the delectable cuisine of France. Now that she has found a true home in Italy, Mimi presents a new Italian cookbook that shares the sumptuous meals she cooks and eats in her Italian home. The 100 recipes in A Kitchen in Italy are Mimi's favorites and the staple dishes she enjoys at home with family and friends. Allow Mimi to transport you to Italy with delectable and accessible meals that celebrate the seasons. In the spring, she loves Risi e Bisi, a brothy, risotto-like Venetian dish served in every home and restaurant when peas are in season. There's no better way to use up abundant summer zucchini than in Spaghetti alla Nerano, a dish that encapsulates the beautiful simplicity of Italian cooking. In the fall, Mimi turns to a comforting Baked Tagliolini with Prosciutto, a luxurious yet uncomplicated baked pasta beloved by her kids. When mandarines and clementines are at their peak in December, pair them with White Chocolate Chip and Pistachio Cookies, made with the very best Sicilian pistachios, for a terrific afternoon snack. With recipes spanning antipasti, primi, secondi, and dolci, you can build a special occasion menu to delight your friends or tuck into a rustic countryside dish on a weeknight. Featuring 150 photographs shot by Mimi's husband, Oddur Thorisson, A Kitchen In Italy brings Mimi's Italian secrets to your dinner table"--